Illusions of Space: Charting Three Dimensions - Glasser, Leslie (ACS Publications, 2014)
We introduce various methods which are used to depict three-dimensional objects on two-dimensional surfaces. Many of these are artistic and not conducive to exact interpretation. Instead, the scientific and engineering practices and mathematics of orthographic projection are introduced, and illustrated in an accompanying interactive Excel workbook. The user may introduce his/her own objects to the workbook, and the resulting illustrations may be used as required. These projection methods are of developing interest and concern as publications increasingly include graphic illustrations of three-dimensional objects, and the principles behind their operations are worthy of consideration and understanding by both instructors and their students.